Bile duct cancer: About three resected cases - Bruno, Gerardo; Rodríguez, Gustavo; Dutto, Gabriel; Navarrete, Héctor; Gutiérrez Galiana, Horacio; Harretche, Martín; Praderi, Raúl C. (Cirugía del Uruguay, 1997)
Three cancers of the choledochus were resected: two by means of segmentary resection of the biliar vía and hepaticojejunostomy and the other by means of cephalic duodenopancreatectomy; the authors analyse diagnostic problems and different surgical procedures that can be used far treatment.